Conjunctive management of surface and groundwater in transboundary watercourses: a first assessment - Lautze, Jonathan F.; Holmatov, B.; Saruchera, D.; Villholth, Karen G. (IWA Publishing, 2018)
Cooperative management of transboundary river basins is widely recognized as important. Emphasis on joint management of shared aquifers has also grown in recent years. Perhaps surprisingly, despite abundant focus on transboundary surface water and growing focus on shared groundwater, there is scant focus on their intersection. To address this knowledge limitation, this article reviews experiences in transboundary water treaties oriented toward different water sources, in order to: i) understand how transboundary water institutions vary according to the water source to which they are oriented, ii) gauge the nature and strength of conjunctive transboundary water management treaties, and iii) identify ways to enhance conjunctive water management in transboundary contexts. The results reveal the existence of more than 50 treaties that make mention of both water sources. Nonetheless, only eight treaties devote ‘substantive’ focus to both surface and groundwater. Review of treaty contents reveals that their focus is on ‘softer’ issues related to institutional development. Moving forward, the reality that the evolution of conjunctive treaties is relatively nascent, and that scope of such treaties is still limited to institutional issues, may indicate large untapped potential – it may be time to outline pathways toward practical implementation of conjunctive water management in transboundary contexts.